The complete mitochondrial genome of a stonefly species, Neoperlops gressitti (Plecoptera: Pelidae) - Guoqiang Zhang; Ying Wang; Jinjun Cao (Mitochondrial DNA. Part B. Resources, 2019)
The small genus Neoperlops only contains four species over the whole world now, and the mitochondrial genome of the genus Neoperlops is still a gap. Here, we report the complete mitochondrial genome of Neoperlops gressitti representing the rare perlid stonefly genus Neoperlops. The circular mitochondrial genome is 15,699 bp in length, which consisting of A (33.30%), G (12.5%), T (29.7%), and C (24.6%), and it is composed of 22 tRNA genes, 13 protein-coding genes (PCGs), two rRNA genes, and a control region like the other published stonefly. In all PCGs, eleven genes initial with the typical start codon ATN, the rest of the two genes (ND1, ND2) with TTG. All PCGs stop with TAG/TAA, except COIII, ND5 use incomplete T—as stop codon. Besides, the phylogenetic result based on the nucleotide of the 13 PCGs and two rRNA genes by using Bayesian (BI) method supports the sister relationship between N. gressitti and Dinocras cephalotes. The complete mitogenome of N. gressitti can provide genetics data to further explore the taxonomic status of Pelidae.